Cross-Sectional Survey of Physician-Reported Usage Patterns and GC–MS Phytochemical Profiling of Mahabala Tailam - Anoop A.K.; P. M. Varier; Ramesh P.R.; Haritha N.; Arjun M.K.; Deepak M.; Venugopalan P (Journal of Pharmaceutical Innovation, 2026)

Post-Harvest Deterioration in Sugarcane Juice Quality and Sucrose Under Different Harvesting Methods and Storage Duration in the Tropical Conditions - Dnyaneshwar N. Borase; Yogesh E. Thorat; Bharat M. Bhalerao; Rajeev Kumar; Rajesh U. Modi; Dinesh Singh; Arjun Singh; Santosh G. Watpade; Prashant P. Patil; Dinesh Singh (Sugar Tech, 2026)

Assessment of district-level climate vulnerability in Kerala using an integrated IPCC framework - K R Riya; B. Ajithkumar; P. Lincy Davis; Arjun Vysakh; R Sarath (Journal of Earth System Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Optimizing Flood Inundation Scenarios: Perspective of Flood Damage and Relief Economics - Susanta Das; B. M. Arjun; Diganta Barman; K. K. Sarma; S. P. Aggarwal (Journal of the Indian Society of Remote Sensing, 2025)

Enhancing resilience with operational hydrometeorological-based flood early warning system in northeast India - Diganta Barman; B M Arjun; Shyam Sundar Kundu; Rekha Bharali Gogoi; Shanbor Kurbah; Anupal Baruah; Aniket Chakravorty; S P Aggarwal (Journal of Earth System Science, 2025)

Spectral Studies of Sm3+-doped Mg2GeO4 Nanophosphors: Realization of Orange-Red Emission for Solid-State Lighting Applications - Akshay Arjun; H. B. Premkumar; G. P. Darshan (Journal of Fluorescence, 2025)

Exploring the effectiveness of bio-formulations from various cattle breeds on pea growth and yield - Arjun Singh; Rameshwar Kumar; Shorya Kapoor; M. S. Bhadwal; A. P. Singh (Organic Agriculture, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Enhancing elevated temperature performance of alkali activated slag-dolomite concrete with Fly ash - Arjun Raj P K; Ravi Joshi; Sarath D; Praveen Nagarajan; Blessen Skariah Thomas (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Whole Genome Mining and Characterization of a New Probiotic Strain Levilactobacillus brevis ILSH3 from Handia: An Ethnic Fermented Beverage of Odisha, India - Manisha Sethi; Arjun OK; Jayalaxmi Dash; Deepti Parida; Salona Kar; Swayambara Mishra; Aliva P. Minz; Anubhab Padhi; Kirti Ranjan Das; Biswaranjan Pradhan; Tulika Prakash; Shantibhusan Senapati (Probiotics and Antimicrobial Proteins, 2025)

The external potassium availability determines the effect of the arbuscular mycorrhizal fungus Rhizophagus irregularis on salinity tolerance in soybeans - Alena P. Jones; Arjun Kafle; Benjamin D. Rose; Summi Dutta; Rachel Vann; Heike Bücking; Kevin Garcia (Symbiosis, 2025)
Arbuscular mycorrhizal (AM) fungi improve water and nutrient acquisition of most land plants. Additionally, they can help plants to alleviate abiotic stresses, such as salinity which causes a major threat for many crop species. Potassium (K + ) plays a major role in plant tolerance to salinity, and we recently demonstrated, by using rubidium (Rb + ) as a proxy, that AM fungi can directly transfer K + to their host plant. Here, we first investigated the impact of K + availability on soybean root development upon salinity. Then, using two-compartment systems, we also inoculated soybean plants with the AM fungus Rhizophagus irregularis , grew them in various K + and sodium (Na + ) regimes, and used Rb + to track K + movements. Root development parameters, biomass, colonization rate, and nutrient concentrations were assessed in AM and non-mycorrhizal plants. Our results show that soybean root development was significantly affected by NaCl treatments, rather than K + availability. Additionally, although the AM symbiosis was drastically reduced by high salinity, it improved K + concentrations and prevented Na + accumulation in inoculated plants, mainly under limiting K + conditions. Rb + transport was observed only when the plants were in demand for K + , but was inhibited by high salinity. Finally, we also show that the addition of NaCl slightly influences the availability of K + and Rb + . This report shows the combined impact of K + availability and AM symbiosis on soybean tolerance to salinity and discusses the limitations of using Rb + as a proxy for K + upon increasing salinity conditions.

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Alkaloid-based modulators of the PI3K/Akt/mTOR pathway for cancer therapy: Understandings from pharmacological point of view - Fatima Zohra Mokhfi; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Bhaskar Vallamkonda; Anitha Balakrishnan; Manjula Challa; Jyoti Singh; P. Dharani Prasad; Syed Salman Ali; et al. (Chemico-Biological Interactions, 2024)

Sub-surface drip-fertigation and legume residue improved maize yield and nitrogen use - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; Kapila Shekhawat; M. C. Meena; R. N. Sahoo; Soora Naresh Kumar; P. K. Upadhyay; Shiva Dhar; Kadagonda Nithinkumar (Nutrient Cycling in Agroecosystems, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Late Quaternary deformation, strain partitioning, and fold-thrust belt widening in the Eastern Himalayan Syntaxis, India - Ishwar Singh; R. Jayangondaperumal; Arjun Pandey; Rao Singh Priyanka; Rajeeb Lochan Mishra; P. Morthekai; Shraddha Jagtap; Pradeep Srivastava; Pankaj Kumar; Sundeep Chopra (Tectonophysics, 2024)

Understanding the physical state and tectonics of Eastern Himalaya using coda wave attenuation - Rohtash Kumar; Amritansh Rai; Raghav Singh; S C Gupta; Arjun Kumar; S P Singh; Prashant Kumar Singh; S P Maurya; Vinay Kumar; G P Singh (Journal of Earth System Science, 2023)

Gloriosa simplex L. (Colchicaceae): a new distributional record for India - S. P. Panda; Titir Saha; Sattom Dasgupta; R. D. Barman; S. K. Arjun; Ravi Prasad; Devendra Singh (Vegetos, 2023)

Heterologous expression of SbAP37-transcription factor in Sesamum indicum L. alleviates salt stress and improves antioxidant enzyme activities - Arjun N. Shetty; Srinath Rao; Havgeppa N. Honnale; Maheshwari Parveda; Rajasamarsen Modi; P. B. Kavi Kishor (Plant Physiology Reports, 2023)

Hydrological-hydrodynamic nexus for predicting flood plain inundation: a case study in Pagladiya-Putimari catchment, India - Diganta Barman; Anupal Baruah; Arjun B. M; Shiv P. Aggarwal (Arabian Journal of Geosciences, 2023)

Holistic framework for flood hazard assessment in a trans-boundary basin - Anupal Baruah; Diganta Barman; Balakrishna Madayala Arjun; Bajitborlang L. Chyne; Shiv P Aggarwal (Acta Geophysica, 2023)

The formaldehyde treated guar meal and prill fat, agro industrial by-products as dietary rumen protected protein and energy source: improves growth performance, feed conversion, nutrient utilization, microbial protein synthesis, blood metabolites and economic efficiency in growing dairy buffalo (Bubalus bubalis) calves - Abhishek B. Parmar; Dilip C. Patel; Nitesh P. Sarvaiya; Ajay P. Parmar; Arjun J. Dhami; Priya J. Ahir (Tropical Animal Health and Production, 2023)

Climate change and more disturbed land-use types will further the invasion of a non-native annual grass, Ventenata dubia - Arjun Adhikari; Jane Mangold; Kumar P. Mainali; Lisa J. Rew (Biological Invasions, 2023)
Identification of suitable habitat for invasive weeds and their projected infestation extent across different land use cover types under a changing climate is crucial for the broad management goals of prevention, detection, and rapid response. In this study, we adopted an ensemble approach of species distribution models to project potential habitat of the invasive annual grass, Ventenata dubia , within the Gallatin County and along its road corridors, in Montana, USA, under current and future climates. The model prediction of V. dubia habitat was excellent with an AUC value of > 0.90. The climate predictors with most influence on V . dubia occurrence were precipitation, potential evapo-transpiration, relative humidity, vapor pressure deficit, and solar radiation for growing season months. Under current climate, the model projected 243 and 1,371 km 2 coverage of V. dubia along road corridors and the entire County, respectively. The projected coverage of V. dubia was greatest for road corridors (239% under RCP4.5 and 302% under RCP8.5) compared to that of Gallatin County (127% under RCP4.5 and 241% under RCP8.5). Among the land use cover types, the model projected greatest expansion of V. dubia across agriculture land with 425% and 484%, and grasslands with 278% and 442% under RCP4.5 and RCP8.5 respectively. Our modelling approach suggests that the changing climate will facilitate spread and establishment of non-native species in disturbed habitats. We conclude that V. dubia with a short history of invasion is expanding at an alarming rate and requires greater investment in detection and monitoring to prevent further expansion.

Moment tensor solutions of some regional events using 3-component single station waveform data - Rohtash Kumar; Arjun Kumar; S C Gupta; S P Singh; Rajeev Saran Ahluwalia; Raghav Singh (Journal of Earth System Science, 2022)

Geospatial approach to elucidate anomalies in the hierarchical organization of drainage network in Kuttiyadi River Basin, Southern India - Thulasi Veedu Swetha; Girish Gopinath; Arun Bhadran; Arjun P. (Frontiers of Earth Science, 2022)

9,10-Dihydro-5-hydroxy-2,3,6-trimethoxyphenanthrene-1,4-dione: a new dihydrophenanthrene from commercial cannabis and its effect on zebrafish larval behaviour - Arjun H. Banskota; Roumiana Stefanova; Joseph P. M. Hui; Fabrice Berrué; John C. Achenbach; Lee Ellis (Natural Product Research, 2022)

The faded stripes of Bengal: a historical perspective on the easternmost distribution of the striped hyena - Muntasir Akash; Arjun Dheer; Stephanie M. Dloniak; Andrew P. Jacobson (European Journal of Wildlife Research, 2021)
The striped hyena ( Hyaena hyaena ) is an understudied large carnivore with no known historic range map. Knowledge of the past and present extent of its easternmost distribution beyond 85° east longitude is dubious. Through a comprehensive review of historical evidence and contemporary records, we investigated striped hyena presence in Bengal, i.e., Bangladesh and the Indian state of West Bengal in South Asia. We found 14 historical records, with the oldest one dating to 1876. Our review establishes Bangladesh as a former striped hyena range country and the striped hyena as one of the first large carnivores to go extinct in Bangladesh. We identified northern Bangladesh as part of its historical range (until ~1965), and south-central Bangladesh as a possible part of its historical range. In West Bengal, India, hyenas were historically present up to the southern tributaries of the Brahmaputra River, but the present range is reduced. The area south of the Damodar River is its last refuge in Bengal. We also found 15 contemporary records (2010–2021) in Bengal, from sites situated on the eastern limit of the Chota Nagpur Plateau. These records noted 25 sightings including 9 deaths due to poaching, train accidents, and retaliatory killings. Our review demonstrates that hyenas are currently present up to 87° east longitude, which extends the currently documented easternmost range for the species by almost 1,000 km. We recommend methods which can be applied to delineate the historical extent of striped hyenas elsewhere as well as for other poorly understood species.

Correction to: Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)

Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)
Invasive plant species are a significant global problem, with the potential to alter structure and function of ecosystems and cause economic damage to managed landscapes. An effective course of action to reduce the spread of invasive plant species is to identify potential habitat incorporating changing climate scenarios. In this study, we used a suite of species distribution models (SDMs) to project habitat suitability of the eleven most abundant invasive weed species across road networks of Montana, USA, under current (2005) conditions and future (2040) projected climates. We found high agreement between different model predictions for most species. Among the environmental predictors, February minimum temperature, monthly precipitation, solar radiation, and December vapor pressure deficit accounted for the most variation in projecting habitat suitability for most of the invasive weed species. The model projected that habitat suitability along roadsides would expand for seven species ranging from + 5 to + 647% and decline for four species ranging from − 11 to − 88% under high representative concentration pathway (RCP 8.5) greenhouse gas (GHG) trajectory. When compared with current distribution, the ensemble model projected the highest expansion habitat suitability with six-fold increase for St. John’s Wort ( Hypericum perforatum ), whereas habitat suitability of leafy spurge ( Euphorbia esula ) was reduced by − 88%. Our study highlights the roadside areas that are currently most invaded by our eleven target species across 55 counties of Montana, and how this will change with climate. We conclude that the projected range shift of invasive weeds challenges the status quo, and requires greater investment in detection and monitoring to prevent expansion. Though our study focuses across road networks of a specific region, we expect our approach will be globally applicable as the predictions reflect fundamental ecological processes.

Effects of Co-Inoculation with Pratylenchus penetrans and Fusarium oxysporum on Growth and Yield of Potato Cultivar Red Norland - Arjun Upadhaya; Guiping Yan; Gary Secor; Andrew P. Robinson (American Journal of Potato Research, 2020)

Extraction of lineaments from different azimuth angles using geospatial techniques: a case study of Pravara basin, Maharashtra, India - Sumit Das; Sudhakar D. Pardeshi; Pallavi P. Kulkarni; Arjun Doke (Arabian Journal of Geosciences, 2018)

Source Parameters and High Frequency Characteristics of Local Events (0.5 ≤ M L ≤ 2.9) Around Bilaspur Region of the Himachal Himalaya - Vandana; Ashwani Kumar; S. C. Gupta; O. P. Mishra; Arjun Kumar; Sandeep (Pure and Applied Geophysics, 2017)

Correlation of human S100A12 (EN-RAGE) and high-sensitivity C-reactive protein as gingival crevicular fluid and serum markers of inflammation in chronic periodontitis and type 2 diabetes - A. R. Pradeep; Santosh S. Martande; Sonender Pal Singh; Deepak Kumar Suke; Arjun P. Raju; Savitha B. Naik (Inflammation Research, 2014)

Disruption of Ion Homeostasis in the Neurogliovascular Unit Underlies the Pathogenesis of Ischemic Cerebral Edema - Arjun Khanna; Kristopher T. Kahle; Brian P. Walcott; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2014)

Numerical Simulation of the 1945 Makran Tsunami on the Southwest Coast and Lakshadweep Islands of India - S. Arjun; Kalarani; P. Dhanya; S. S. Praveen; A. K. Reshmi; N. P. Kurian; M. V. Ramana Murthy; T. S. Shahul Hameed; T. N. Prakash (Marine Geodesy, 2011)

Numerical Simulation of the December 26, 2004, Tsunami on the Southwest Coast and Lakshadweep Islands of India - S. S. Praveen; A. K. Reshmi; P. Dhanya; S. Arjun Kalarani; N. P. Kurian; M. V. Ramana Murthy; T. S. Shahul Hameed; T. N. Prakash (Marine Geodesy, 2011)

Prioritization of candidate SNPs in colon cancer using bioinformatics tools: An alternative approach for a cancer biologist - C. George Priya Doss; R. Rajasekaran; P. Arjun; Rao Sethumadhavan (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Tidal Constituents in the Shallow Waters of the Southwest Indian Coast - S. Arjun; L. Sheela Nair; V. R. Shamji; N. P. Kurian (Marine Geodesy, 2010)

Wind waves and sediment transport regime off the south-central Kerala coast, India - N. P. Kurian; K. Rajith; T. S. Shahul Hameed; L. Sheela Nair; M. V. Ramana Murthy; S. Arjun; V. R. Shamji (Natural Hazards, 2009)